2021
DOI: 10.1029/2020gh000351
|View full text |Cite
|
Sign up to set email alerts
|

Himalaya Air Quality Impacts From the COVID‐19 Lockdown Across the Indo‐Gangetic Plain

Abstract:  The COVID-19 lockdown provides an opportunity to the assess the impact of air pollution from the Indo-Gangetic Plain on the Himalaya.  Air pollutions levels in cities in the western Indo-Gangetic Plain experienced marked drops that coincided with the lockdown.  Across the Indo-Gangetic Plain and Himalaya, there were reductions in air pollution in the west and increases in the east.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…There are a number of assessments conducted on a national, regional, or global scale investigating the association between the COVID-19 lockdown and air quality (Dasgupta and Srikanth, 2020;Madineni et al, 2021;Moore and Semple, 2021;Nigam et al, 2021;Pozzer et al, 2020;Prakash et al, 2021;Sannigrahi et al, 2021;Tang et al, 2021;Upadhyay et al, 2022). Those studies have shown a mix of findings with marked spatial heterogeneity in the change in air quality parameters during the lockdown period compared to the baselines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of assessments conducted on a national, regional, or global scale investigating the association between the COVID-19 lockdown and air quality (Dasgupta and Srikanth, 2020;Madineni et al, 2021;Moore and Semple, 2021;Nigam et al, 2021;Pozzer et al, 2020;Prakash et al, 2021;Sannigrahi et al, 2021;Tang et al, 2021;Upadhyay et al, 2022). Those studies have shown a mix of findings with marked spatial heterogeneity in the change in air quality parameters during the lockdown period compared to the baselines.…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, a countrywide lockdown was imposed from 24 March to 20 July to contain the spread of the SARS-CoV-2 virus during the first wave of the COVID-19 pandemic. The air quality change during lockdowns are not geographically uniform and are determined by a mix of factors, such as major air pollutant sources, and the meteorology and topography of a region (Gao et al, 2021;Moore and Semple, 2021;Tang et al, 2021;Upadhyay et al, 2022). A recent study analyzed the change in air quality over the South Asia region, where Nepal is located, during a narrow window (25 March-30 April 2020; dry season) of the lockdown period (Upadhyay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%